SALM4 negatively regulates NMDA receptor function and fear memory consolidation - Eunkyung Lie (Nature Portfolio, 2021)
To elucidate the role of synaptic cell adhesion-like molecule 4 (SALM4) in altering synaptic function in the context of fear memory, Lie at al performed behavioural and electrophysiological assessments of SALM4 knockout mice undergoing cued fear, spatial, and object-recognition memory tasks. They demonstrated that SALM4 suppresses heightened GluN2B-expressing NMDA receptor function specifically during fear memory consolidation.